The effects of dietary fat source and feeding duration on pig growth performance and fat quality - Stephenson, Ethan Wade (Kansas State University, 2015)
In 3 experiments, 4,720 pigs were used to determine the effects of: 1) dietary fat and feeding duration on growth performance and fat quality in finishing pigs; or 2) a novel protease or 3) increasing levels of Zn amino acid complex (ZnAA) or ZnO on finishing pig performance. Experiment 1 tested the effects of feeding tallow, soybean oil, or a blend of the two for various feeding durations (d 0 to 42, 42 to 84, or 0 to 84). Overall, pigs fed added fat for the entire 84 d had improved G:F compared to those fed a control diet. Additionally, pigs fed additional fat for the entire study had improved ADG and G:F as well as increased d 84 BW compared to pigs fed additional fat for 42 d. Increasing the feeding duration of soybean oil lowered monounsaturated fatty acids and increased polyunsaturated fatty acid concentrations while these values remained relatively unchanged by the addition of tallow. There were feeding period by fat source interactions for fatty acid composition and iodine value for belly and backfat, but not jowl fat, indicating a longer turnover rate for jowl fat compared to belly or backfat. In Exp. 2, adding a protease to a nutrient deficient diet increased ADFI and tended to increase ADG compared to pigs fed a negative control diet. There were no differences observed in ADG, ADFI, or G:F between pigs fed a positive control diet, formulated to 90% of the pigs SID lysine requirement, and those fed a negative control diet plus the protease, which would suggest the release values attributed to the enzyme were accurate. In Exp. 3, supplementing additional Zn from either ZnAA or ZnO at 25, 50, or 75 ppm in finishing diets for commercial finishing pigs was evaluated. Overall, no differences were observed in ADFI, but a Zn source by level interaction was observed for ADG and G:F, as pigs fed increasing ZnO were observed to have similar performance, while pigs fed added levels of 25 and 50 ppm Zn from ZnAA had decreased performance compared to those fed the highest level of ZnAA.
Keywords: carcass; finishing pig; growth; iodine value; soybean oil; tallow; Agriculture, General (0473)